The prevalence and characteristics of and the association between MIH and HSPM in South‐Western France. Issue 3 (27th December 2022) - Estivals, Julia; Fahd, Caroline; Baillet, Jeanne; Rouas, Patrick; Manton, David John; Garot, Elsa
Abstract: Background: Molar–incisor hypomineralisation (MIH) and hypomineralised second primary molars (HSPM) involve qualitative structural developmental anomalies of tooth enamel, affecting the first permanent molars (FPM) and the second primary molars, respectively. This developmental anomaly of systemic origin has important consequences for oral health. Aim: To determine the prevalence of MIH and HSPM in south‐western France and explore the distribution of hypomineralised lesions on permanent and primary molars. Design: Amongst 856 children (aged 7–9 years) in schools randomly selected by the Academy of Bordeaux (Ministry of Education), the FPM, permanent incisors and the second primary molars were examined by two examiners trained and calibrated for the diagnostic criteria for MIH and HSPM of the European Academy of Paediatric Dentistry. Results: Molar–incisor hypomineralisation was present in 160 children (18.7%) and HSPM in 81 children (9.5%); 4.9% had both HSPM and MIH (42 of 856). Hypomineralised lesions were present in 1–4 FPM in affected individuals (mean = 2.4) and were distributed in an asymmetrical manner with widely varying severity at the tooth and individual level. A child with HSPM was more likely to have MIH than a child without HSPM (95% CI OR = 6.0 [3.7–9.7]; p  < .0001). Conclusion: Molar–incisor hypomineralisation and HSPM have three main asymmetrical characteristics: tooth location, severity of hypomineralisation and number of teeth affected.